Digital engagement and healthcare service selection: Insights into young consumers decision-making in the digital era - Siwi Dyah Ratnasari; Tita Hariyanti; Pardiman Pardiman; Nevi Danila (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2026)
Digital transformation has fundamentally changed how young healthcare consumers select hospitals, shifting decision-making beyond clinical quality toward digitally mediated experiences. Despite the rapid digitalization of healthcare services, limited research explains how digital engagement and experiential value jointly shape hospital choice from a service marketing perspective. Using a qualitative phenomenological approach, this study analyzed in-depth interviews with 11 young healthcare consumers in a medium-sized Indonesian city. Five determinants emerged: digital visibility, online interaction quality, facility comfort, patient reviews, and perceived emotional value. The findings demonstrate that digital touchpoints and experiential value play a central role in hospital choice. This study extends consumer behavior and service marketing literature by integrating digital engagement and emotional value into hospital choice behavior. Although the findings are context-specific, they offer strategic insights for healthcare organizations to strengthen competitiveness through digitally integrated, patient-centered marketing strategies that enhance engagement, trust, and long-term loyalty.